Fact or Fiction? Children's Preferences for Real Versus Make-Believe Stories. (March 2015) - Barnes, Jennifer L.; Bernstein, Emily; Bloom, Paul
Some children and adults are more drawn to the imaginary than others. Here, we examine whether developmental differences also play a role in the degree to which individuals are drawn to make-believe stories over real ones (or vice versa). Experiment 1 explored the influence of the factuality of stories—whether or not stories reflect events that had actually happened—on children's story preferences. Experiment 2 explored the effect of magical versus realistic content on participants' story preferences. Age differences were found for both manipulations. The results suggest that despite the surplus of imaginary activity associated with childhood, young children are not more prone to liking "un-real" stories than adults and may in fact like them less.